Village Homes Solar House Designs: a collection of 43 energy-Conscious house - Bainbridge, David. Corbett, Judy. Hofacre, John (Estados Unidos de América, 1979)
Trata de fomentar un sentido de comunidad y para la conservación de energía y recursos naturales.
1. Water wall 2. The solar homes of village homes
incluye índice
Col. Educ
Keywords: 1. SIMPLE PASSIVE 2. SPECIAL FEATURES